Genetic Diversity Of The Beetle, Paederus Fuscipes Curtis (Coleoptera: Staphylinidae) And Its Symbiotic Diversity With Pederin Polymorphism Based On 16S Rrna Metagenomics Profiling - Teoh, Miao Ching (2023)
Paederus rove beetles are known to carry the pederin toxin that causes linear dermatitis when crushed on skin. The toxin is produced by an unculturable Pseudomonas sp. harboured by the female Paederus beetles. Pederin polymorphism has been observed several Paederus and Paederidus beetle species wherein the (+) female beetles carried the toxin pederin and (−) females lacking this toxic amide. It has been stated that the (−) female Paederus beetles are infected with more bacterial species than (+) females, but the microbial profiles between the two female groups were not revealed. Besides, the association of pederin polymorphism with the host beetle’s genetic is yet to be investigated. Herein, the objectives of this dissertation are to investigate the microbial profile of the two groups of P. fuscipes beetles, and to study the host beetle’s mtDNA COI in association with pederin polymorphism. Pederin polymorphism studies on P. fuscipes beetles were carried out by PCR detection of pederin (ped) biosynthesis genes. The female beetles were then subjected to 16S rRNA amplicon sequencing and mtDNA COI analysis. This study also attempts to culture and isolate the pederin-producing bacteria.